Clinical Efficacy of Laparoscopic Orchiopexy With the Modified Prentiss Maneuver for Non-palpable Testis Near the Internal Ring - He, Tian-Qu; Tong, Fang-Yun; Wang, Zhi; Liu, Yu; Hu, Jian-Jun; Chen, Yi-Fu; Tu, Lei; He, Jun; Zhao, Yao-Wang (Frontiers in Pediatrics, 2022)
Objective: To compare the clinical efficacy and safety of laparoscopic orchiopexy with the modified Prentiss manoeuvre (LOMPM) and laparoscopic trans-inguinal orchiopexy (LTIO) for the treatment of non-palpable testis (NPT) less than 1 cm from the internal ring.Methods: Children with unilateral NPT who underwent laparoscopic orchiopexy at our center between February 2018 and January 2021 were retrospectively analyzed. According to the surgical method, they were divided into LOMPM and LTIO groups. The operation time, postoperative pain degree, postoperative complications and follow-up results were compared between the two groups.Results: A total of 98 patients were included in this study, including 41 cases in the LOMPM group and 57 cases in the LTIO group. All patients underwent successful surgery. The LOMPM group was superior to the LTIO group in terms of postoperative testicular position (lower scrotm: 90.2% vs 71.9%, P=0.026). There were no significant differences in operation time, postoperative pain score, and complications between the two groups. Preoperative testicular volume, postoperative testicular volume, and testicular growth rate in the LOMPM group were comparable to those in the LTIO group. There were no testicular atrophy, inguinal hernia and hydrocele in both groups after operation.Conclusions: LOMPM was comparable in safety to LTIO, but LOMPM had a good post-operative testicular position, and was suitable for the treatment of NPT near the internal ring.